2001
DOI: 10.1074/jbc.m007003200
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Prolyl Oligopeptidase Substrate/Inhibitor Complexes

Abstract: Structure determination of the inactive S554A variant of prolyl oligopeptidase complexed with an octapeptide has shown that substrate binding is restricted to the P4-P2 region. In addition, it has revealed a hydrogen bond network of potential catalytic importance not detected in other serine peptidases. This involves a unique intramolecular hydrogen bond between the P1 amide and P2 carbonyl groups and another between the P2 amide and N⑀2 of the catalytic histidine 680 residue. It is argued that both hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…Nevertheless, during the long crystallization period the substrates were cleaved so that only the acyl parts of the substrates were seen in the electron density maps. These enzyme-product complexes share identical binding modes to the enzyme-substrate complexes determined previously (18). In the case of subtilisin modified also at the active site serine residue, an ϳ10 6 -fold decrease in activity was demonstrated with kinetic analysis (34), indicating a small remaining activity, but with a different mechanism.…”
Section: Table IV Kinetic and Activation Parameters For The Reactionsmentioning
confidence: 62%
See 4 more Smart Citations
“…Nevertheless, during the long crystallization period the substrates were cleaved so that only the acyl parts of the substrates were seen in the electron density maps. These enzyme-product complexes share identical binding modes to the enzyme-substrate complexes determined previously (18). In the case of subtilisin modified also at the active site serine residue, an ϳ10 6 -fold decrease in activity was demonstrated with kinetic analysis (34), indicating a small remaining activity, but with a different mechanism.…”
Section: Table IV Kinetic and Activation Parameters For The Reactionsmentioning
confidence: 62%
“…Therefore, we examined the effects on the kinetic and thermodynamic parameters of the glutamic acid residue located at various sites of the leader peptide, Abz-Gly-Phe-Ser-ProPhe(NO 2 )-Arg-Ala, which corresponds to the P1-P4 amino acids of bradykinin, a possible natural substrate. Our previous x-ray crystallographic studies on the binding of an octapeptide indicated that the P3-P2Ј residues were clearly associated with the enzyme, whereas the P4 residue might bind weakly (18). Yet, we have also extended the position of Glu toward subsites 4 and 5, because it is known from the three-dimensional structure of prolyl oligopeptidase (20) that Arg-252 and Arg-128 are not far from the binding site so that they may form appropriate subsites for the binding of Glu in those positions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations